2007
DOI: 10.1002/jcb.21156
|View full text |Cite
|
Sign up to set email alerts
|

In silico determination of intracellular glycosylation and phosphorylation sites in human selectins: Implications for biological function

Abstract: Post-translational modifications provide the proteins with the possibility to perform functions in addition to those determined by their primary sequence. However, analysis of multifunctional protein structures in the environment of cells and body fluids is made especially difficult by the presence of other interacting proteins. Bioinformatics tools are therefore helpful to predict protein multifunctionality through the identification of serine and threonine residues wherein the hydroxyl group is likely to bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 71 publications
(73 reference statements)
0
6
0
Order By: Relevance
“…De‐phosphorylation of the Ser/Thr may result in a possibility of an addition of O GlcNAc on the OH function of the same Ser/Thr. Thus, blocking the phosphorylation on those specific sites, consequently resulting in blocking of the function regulated by phosphorylation such as described earlier [Ahmad et al, 2006, 2007].…”
Section: Ptms Switchboard In Oct‐1mentioning
confidence: 96%
“…De‐phosphorylation of the Ser/Thr may result in a possibility of an addition of O GlcNAc on the OH function of the same Ser/Thr. Thus, blocking the phosphorylation on those specific sites, consequently resulting in blocking of the function regulated by phosphorylation such as described earlier [Ahmad et al, 2006, 2007].…”
Section: Ptms Switchboard In Oct‐1mentioning
confidence: 96%
“…In addition, glycosylation and phosphorylation motifs were identified on the metalloprotease sequence. The presence of these motifs suggested that the 07/ 118 T2 metalloprotease could be subject to post-translational modifications which can enable it to perform functions other than those determined by its primary sequence (Ahmad et al, 2007). Furthermore, it was shown that the HEXXH metalloprotease family is the only family of this protease group that is extensively modified post-translationally by both N-glycosylation and glycosyl phosphatidylinositol (McGwire and Chang, 1996).…”
Section: Molecular Evidences Of Thermostable Metalloprotease(s) In Vmentioning
confidence: 97%
“…Multiple putative asparagines have been identified in Na V 1.5 as potential N-linked glycosylation sites (Ahmad et al, 2007). However, thus far only asparagines in the ancillary Na V β1 subunit have been demonstrated to functionally modify the cardiac Na + current, by causing leftward shifts of the inactivation and activation curves, promoting fast inactivation, and slowing RFI (Ednie et al, 2013; Stocker & Bennett, 2006; Ufret-Vincenty et al, 2001).…”
Section: Regulation Of Cardiac Nav15mentioning
confidence: 99%